Investigating Facial Muscle Physiology Following Soft Tissue Filler Injections—A Surface-derived Electromyographic and Skin Vector Displacement Analytic Study - Casabona, Gabriela; Frank, Konstantin; Zeng, Rui; Cotofana, Sebastian; Alfertshofer, Michael; Weinmann, Charlotte; Moellhoff, Nicholas; Kaye, Kai O. (Facial Plastic Surgery, 2024)
The use of hyaluronic acid-based soft tissue fillers has often been reported to modulate the muscle, that is, to cause myomodulation. To our knowledge, there has been so far no scientific study investigating the potential of hyaluronic acid-based soft tissue fillers to modulate or actually alter the function of facial muscles. To further assess this three-dimensional (3D) surface imaging and electromyography (EMG)-based prospective study investigated the changes of facial muscle contraction after injection of strategically placed hyaluronic acid-based soft tissue fillers to assess the actual validity of the term myomodulation. A total of 13 subjects with a mean age of 37.8 years (12 females, 1 male) were injected according to a predefined injection protocol. Surface EMG and 3D surface imaging were performed prior to the injection and 5 days after the injection. The results showed no significant change in the strength of the muscles (measured in μV) after injection of hyaluronic acid-based soft tissue fillers. However, horizontal and vertical skin displacement upon contraction of the zygomaticus major muscle changed significantly between baseline and follow-up, with a mean horizontal skin displacement increase from 3.2 to 4.1 mm. Upon contraction of the depressor anguli oris muscle, the horizontal skin displacement did not change significantly (2.15 vs. 2.05 mm), while vertical skin displacement increased significantly from 2.9 to 4.3 mm. The modification of the surrounding tissue caused an alteration of the vectorial skin displacement upon contraction of the muscle. A potential explanation could be the increased distance between the origin and insertion of the muscle due to the material deposition in the proximity of the relevant facial muscles, leading to a change of contraction vector.
Keywords: myomodulation; soft tissue filler; EMG; 3D imaging